Estimation of genetic and phenotypic trends for dairy traits of Gyr and Guzerá breeds (Acta Scientiarum. Animal Sciences, 2017)
Milk production has high economic importance in dairy cattle production systems, which justifies its inclusion in genetic breeding programs. The objective of this study was to evaluate the genetic and phenotypic trends of dairy traits in Gyr (167 lactations) and Guzerá (148 lactations) breeds in the State of Rio Grande do Norte (RN). Milk, fat and protein production obtained from monthly dairy controls were the traits evaluated. The expected differences in progeny (DEPs) for these traits were estimated using an animal model. From the means of phenotypic values and DEPs, we estimated the genetic and phenotypic trends in linear regressions as a function of the year of calving of the animal. Positive genetic and phenotypic trends were observed for Gyr (26.8 and 88.7 kg year-1) and Guzerá (8.44 and 37.68 kg year-1). Gyr breed presented positive genetic trends for fat (1.08 kg year-1) and protein (0.45 kg year-1) production and the Guzerá breed showed positive genetic trends for fat (0.36 kg year-1) and protein (0.25 kg year-1) production. The selection applied in the evaluated herds has produced satisfactory genetic and phenotypic progress for milk, fat and protein production.